2023
DOI: 10.35848/1882-0786/acb310
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of spin-transfer-torque efficiency using magnetization reversal against a magnetic field: comparison of FeCr with negative spin polarization and NiFe

Abstract: We propose and demonstrate an experimental method to evaluate spin-transfer-torque (STT) efficiency in current-perpendicular-to-plane giant magnetoresistance devices, which utilizes STT-induced magnetization reversal against a perpendicular magnetic field. Using, this method, we estimated the STT efficiency of FeCr with negative spin polarization, which attracts attention in spintronics applications. In comparison with NiFe with positive spin polarization, the sign of the STT from FeCr was opposite, reflecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In negative spin polarization materials, the spin momentum direction of the spin-polarized conduction electron is opposite to the magnetization direction. 16,17 This relation is in contrast to the standard positive spin polarization found in the aforementioned Co-based Heusler alloys and many other spintronic materials. Intriguingly, negative spin polarization materials can reverse the signs of MR and STT.…”
Section: Introductionmentioning
confidence: 62%
“…In negative spin polarization materials, the spin momentum direction of the spin-polarized conduction electron is opposite to the magnetization direction. 16,17 This relation is in contrast to the standard positive spin polarization found in the aforementioned Co-based Heusler alloys and many other spintronic materials. Intriguingly, negative spin polarization materials can reverse the signs of MR and STT.…”
Section: Introductionmentioning
confidence: 62%
“…Initially, a spin-polarized current through a ferromagnetic (FM) layer was used to drive the DWs. This effect is known as the spin-transfer torque. Around a decade ago, it was found that the current density for driving the DWs can be reduced at least by a factor of 10 by utilizing the spin–orbit torque (SOT) from the heavy metal layer, deposited adjacent to the FM layer. , Therefore, Sengupta et al emulated the functionalities of energy-efficient neurons and synapses using a SOT-driven DW-magnetic tunnel junction (MTJ) device in 2015. ,, …”
Section: Introductionmentioning
confidence: 99%